BUDAYA KERJA DAN GAYA KEPEMIMPINAN : LITERATURE REVIEW - Dwi Arini Mandasari; Helmi Buyung Aulia Safrizal (BADAN PENERBIT STIEPARI PRESS, 2023)
Organizational Culture Theory is an approach in the field of management studies that examines how organizational culture influences the behavior, decisions, and performance of individuals within an organization. On the other hand, leadership style refers to the approach or style used by a leader to influence and guide members of an organization. This research utilizes the Literature Review method with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) approach to explore the scope of Organizational Culture and Leadership Style according to previous studies, the impact of Organizational Culture and Leadership Style on Performance according to previous research, and other related variables. The findings obtained from the identification of 27 articles indicate that 89% of the articles provide evidence that Organizational Culture has a significant positive impact on Employee Performance, and 63% of the articles demonstrate that Leadership Style has a significant positive impact on Performance. Other related variables include Work Motivation, Organizational Commitment, Organizational Restructuring, Job Satisfaction, Work Environment, Management Control System, Work Ethic, Work Environment, and Employee Engagement.